Exposure to the environmentally-persistent insecticide chlordecone induces detoxification genes and causes polyp bail-out in the coral P. damicornis. (March 2018) - Wecker, Patricia; Lecellier, Gaël; Guibert, Isis; Zhou, Yuxiang; Bonnard, Isabelle; Berteaux-Lecellier, Véronique
Abstract: Marine ecosystems are both stressed and threatened by pesticides that are used on land. Nevertheless, research on the impact of pesticides on coral reefs and the underlying mechanisms is still in its infancy. The insecticide chlordecone is a persistent organic pollutant with carcinogenic effects in rats and mice. Chlordecone has been detected in diverse marine organisms in the Caribbean, but unexpectedly, also in French Polynesia. We combined transcriptomic and morphologic analyses of analyses the response of the coral Pocillopora damicornis to chlordecone stress. We compared chlordecone stress with thermal stress to determine a chlordecone-specific response. We found eight transcripts related to the P450-1A or P450-3A families that were specifically overexpressed in response to chlordecone. There was also sequential overexpression of transcripts involved in apoptosis and degradation of cellular matrix proteins. Finally, we report the first observation of chlordecone-induced P. damicornis polyp bail-out. Altogether, these results strongly suggest that apoptosis and expression of genes belonging to the cathepsin family are sequentially regulated processes leading to coenosarc dissociation and loss. Highlights: First report of a transcriptomic time series analysis associated to a scleractinian polyp bail-out. After acidification, salinity, potassium and herbicide, the first observation of an insecticide induced polyp bail-out. The involvement of P450-1A and -3A subfamily genes in the detoxification process could suggest new medical research. Regulation of genes belonging to apoptosis and to cathepsin family led to coenosarc dissociation and loss of colonial form.